The inhibition of PI3K and NF kappa B promoted curcumin-induced cell cycle arrest at G2/M via altering polyamine metabolism in Bcl-2 overexpressing MCF-7 breast cancer cells - Akkoç, Yunus; Çoker Gürkan, Ajda; Palavan Ünsal, Zeynep Narçın; Berrak, Özge; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (Elsevier France-Editions Scientifiques Medicales Elsevier, 23 Rue Linois, 75724 Paris, France, 2016)
Bcl-2 protein has been contributed with number of genes which are involved in oncogenesis. Among the many targets of Bcl-2, NF kappa B have potential role in induction of cell cycle arrest. Curcumin has potential therapeutic effects against breast cancer through multiple signaling pathways. In this study, we investigated the role of curcumin in induction of cell cycle arrest via regulating of NF kappa B and polyamine biosynthesis in wt and Bcl-2+ MCF-7 cells. To examine the effect of curcumin on cell cycle regulatory proteins, PI3K/Akt, NF kappa B pathways and polyamine catabolism, we performed immunoblotting assay. In addition, cell cycle analysis was performed by flow cytometry. The results indicated that curcumin induced cell cycle arrest at G2/M phase by downregulation of cyclin B1 and Cdc2 and inhibited colony formation in MCF-7 wt cells. However, Bcl-2 overexpression prevented the inhibition of cell cycle associated proteins after curcumin treatment. The combination of LY294002, PI3K inhibitor, and curcumin induced cell cycle arrest by decreasing CDK4, CDK2 and cyclin E2 in Bcl-2+ MCF-7 cells. Moreover, LY294002 further inhibited the phosphorylation of Akt in Bcl-2+ MCF-7 cells. Curcumin could suppress the nuclear transport of NF kappa B through decreasing the interaction of P-I kappa B-NF kappa B. The combination of wedelolactone, NF kappa B inhibitor, and curcumin acted different on SSAT expression in wt MCF-7 and Bcl-2+ MCF-7 cells. NF kappa B inhibition increased the SSAT after curcumin treatment in Bcl2 overexpressed MCF-7 cells. Inhibition of NF kappa B activity as well as suppression of ROS generation with NAC resulted in the partial relief of cells from G2/M checkpoint after curcumin treatment in wt MCF7 cells. In conclusion, the potential role of curcumin in induction of cell cycle arrest is related with NF kappa B-regulated polyamine biosynthesis. (C) 2015 Elsevier Masson SAS. All rights reserved.
Keywords: Curcumin; Cell cycle; Bcl-2; NF kappa B; Phosphatidylinositol 3-Kinase; Targeting Bcl-2; Induced Apoptosis; Pathway; Growth; Activation; Expression; Proliferation; D1; Phosphorylation